The Role of Radionuclide Diagnostic Methods in Neuro-Oncology - T. Yu. Skvortsova; N. Judov; M. Plotkin; G. Stoffels; N. Galldiks; R. N. Krasikova; K. J. Langen (Вестник рентгенологии и радиологии)
In recent years, positron emission tomography (PET) with amino acid radiopharmaceuticals has assumed increasing importance in the diagnosis of brain tumors and it has already become an additional method of examination along with magnetic resonance imaging (MRI) in many diagnostic centers. The markers of somatostatin receptors seem to be most promising for the PET diagnosis of meningiomas. PET provides important additional information in the diagnosis of brain changes of unknown origin and more accurate information about tumor boundaries, which is necessary for biopsy, neurosurgery, and radiation therapy. In addition, labeled amino acid PET aids in the assessment of disease prognosis, in the differentiation of continued tumor growth from nonspecific therapeutic pathomorphism of the brain, and in the evaluation of treatment efficiency at an earlier time than is possible with MRI.